(untitled) (Current Horticulture, 2024)
The experiment was designed in Randomized Block Design in four replications with seven treatments, i.e. T1 - control (only water), T2 –Trichoderma viride 5%, T3-Trichoderma viride 10%, T4 - Pseudomonas 5%, T5 -Pseudomonas 10%, T6 -biofertisol 5% and T7 - biofertisol 10%, at Department of Horticulture, JNKVV, Jabalpur, in 8 year old guava (Psidium guajava L.) variety L 49, during 2020- 21 and 2021-22. Foliar application of Trichoderma @ 10 % was most beneficial for growth, yield and quality parameters. Trichoderma @ 10 % recorded maximum increment in shoot length, plant height, canopy height, leaf chlorophyll Index, chlorophyll content index, LAI. Foliar application of 10% Trichoderma wasalso superior in yield parameter found maximum number of flowers shoot, fruit set percentage, fruit retention percentage, fruits/shoot, fruit/splant, yield/plant, fruit length, fruit width, fruit weight, fruit volume, pulp weight/fruit and pulp per cent. Total soluble solids, total sugar, and reducing sugar were recorded in Trichoderma 10% (T7) and minimum acidity was recorded in foliar application of Pseudomonas 10% (T5) .